"I'm listening, did it make any difference to your negative emotions?" Evidence from hyperscanning. (25th September 2022) - Wang, Shuyin; Lu, Jiamei; Yu, Meiqi; Wang, Xia; Shangguan, Chenyu
Highlights: Active listening is an important part of interpersonal emotion regulation. When individuals were engaged in active listening, the OFC, left dlPFC, right dlPFC, and right TPJ were significantly activated in the participant whose emotions were regulated, whereas the OFC, left dlPFC, and right TPJ were significantly activated in the emotion regulator. Band analysis showed significant IBS increments in the mPFC, OFC, right dlPFC, right TPJ, and left dlPFC at different frequencies when individuals were engaged in active listening. Abstract: Hyperscanning refers to simultaneously recording the brain activity of two or more people participating in the same cognitive activity to reveal the underlying processes. Active listening is a necessary and important part of interpersonal emotional regulation; however, few studies have addressed the corresponding brain activity. Therefore, this study aims to explore the regulatory effect of active listening and changes in the brain using functional near-infrared optical spectroscopy(fNIRS) in real situations requiring interpersonal emotional regulation. Behavioral results show that active listening has a significant effect on improving individuals' negative emotions. According to the neuroimaging results, the orbitofrontal cortex (OFC), right dorsolateral prefrontal cortex (right dlPFC), right temporoparietal junction (right TPJ), and left dorsolateral prefrontal cortex (left dlPFC) were significantly activated. In addition, band analysis showed interpersonal brain synchronization (IBS) increments at the orbitofrontal cortex (OFC), right dlPFC, right TPJ, and left dlPFC at different frequencies. Measurements of IBS and behavioral coherence showed that the increases of IBS at the OFC, right dlPFC, right TPJ, and left dlPFC were not significantly correlated with depression, anxiety, and the empathy level of the emotional regulator. The present study provides brain imaging evidence for the effectiveness of active listening in interpersonal emotional regulation.